Spatio-Temporal Variability in North Atlantic Oscillation Monthly Rainfall Signatures in Great Britain - Harry West; Nevil Quinn; Michael Horswell (Atmosphere, 2021)
The North Atlantic Oscillation (NAO) is the primary atmospheric-oceanic circulation/teleconnection influencing regional climate in Great Britain. As our ability to predict the NAO several months in advance increases, it is important that we improve our spatio-temporal understanding of the rainfall signatures that the circulation produces. We undertake a high resolution spatio-temporal analysis quantifying variability in rainfall response to the NAO across Great Britain. We analyse and map monthly NAO-rainfall response variability, revealing the spatial influence of the NAO on rainfall distributions, and particularly the probability of wet and dry conditions/extremes. During the winter months, we identify spatial differences in the rainfall response to the NAO between the NW and SE areas of Britain. The NW area shows a strong and more consistent NAO-rainfall response, with greater probability of more extreme wet/dry conditions. However, greater NAO-rainfall variability during winter was found in the SE. The summer months are marked by a more spatially consistent rainfall response; however, we find that there is variability in both wet/dry magnitude and directionality. We note the implications of these spatially and temporally variable NAO-rainfall responses for regional hydrometeorological predictions and highlight the potential explanatory role of other atmospheric-oceanic circulations.